Identification of Multigene Biomarker for Shrimp White Feces Syndrome by Full-Length Transcriptome Sequencing - Zeng, Shenzheng; Zhou, Renjun; Bao, Shicheng; Li, Xuanting; Deng, Zhixuan; Hou, Dongwei; Weng, Shaoping; He, Jianguo; Huang, Zhijian (Frontiers in Genetics, 2020)
The Pacific white shrimp, Litopenaeus vannamei, with the largest shrimp industry production in the world, is currently threatened by a severe disease, white feces syndrome (WFS), which cause devastating losses globally, while its causal agents remain largely unknown. Herein, compared to the Control shrimp by metagenomic analysis, we firstly investigated that the altered functions of intestinal microbial community in WFS shrimp were the enrichment of bacterial chemotaxis and flagellar assembly pathways, hinting at a potential role of pathogenic bacteria for growth and development, which might be related to WFS occurrence. Single-molecule real-time (SMRT) sequencing was to further identify the gene structure and gene regulation for more clues in WFS aetiology. Totally 50,049 high quality transcripts were obtained, capturing 39,995 previously mapped and 10,054 newly detected transcripts, which were annotated to 30,554 genes. A total of 158 differentially expressed genes (DEGs) were characterized in WFS shrimp. These DEGs were strongly associated with various immune related genes that regulated the expression of multiple antimicrobial peptides (e.g. anti-lipopolysaccharide factors, penaeidins and crustin), which were further experimentally validated using quantitative PCR on transcript level. Collectively, multi-gene biomarkers were identified to be closely associated with WFS, especially those functional alterations in microbial community and the upregulated immune related gene with antibacterial activities. Our finding not only inspired our cogitation on WFS aetiology from both microbial and host immune response perspectives with combined metagenomic and full-length transcriptome sequencing, but also provided valuable information for enhancing shrimp aquaculture.